Balancing academics and motherhood: exploring role navigation with new mothers in counselor education doctoral programs - Bethea Johnson, Emily (Kansas State University, 2022)
This qualitative interview study study seeks to examine the unique perspectives of mothers in counselor education programs through a feminist lens. In this stage of research, the study inspects the lived experiences of three female graduate students who have become biological mothers during their doctoral journeys and who are now actively enrolled in their last two years of their doctoral programs. In addition to examining this population, the study sought to explore these experiences through the lens of role theory (specifically how mothers experience and navigate these identity intersections) and also utilized feminist tenets as an attitudinal method and extension of the reflexive qualitative interviewing processes. This research studied the experiences of women in doctoral counselor education environments such as role navigation, academic motherhood, and the impact of supportive relationships with other participants, mentors, faculty, family, and community in these types of educational formats. Through In Vivo coding analysis of the data, themes of support, navigation, and pressures were identified. Select sub-themes include family, community, and academic supports, schedule flexibility, time usage, childcare, guilt, loss, stress, and loneliness.
Keywords: Counselor education; Academic motherhood; Role navigation; New mothers; Doctoral programs; Doctoral mothers; Community support